2007
DOI: 10.1097/bot.0b013e3180616ba5
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Phosphate Cement Augmentation of the Femoral Neck Defect Created After Dynamic Hip Screw Removal

Abstract: This study demonstrates that augmentation of the bony defect created by dynamic hip screw removal with reinforced calcium phosphate cement significantly improved the failure strength of the bone. Cement augmentation after hardware removal may decrease the risk of refracture and allow early weightbearing, especially in elderly patients with osteoporotic bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 18 publications
0
34
0
4
Order By: Relevance
“…Besides, other successful attempts have been made to use these formulations for calcaneal fractures [509], hip fractures [510,511], augmentation of osteoporotic vertebral bodies [512], distal radius fractures [513], tibial plateau fractures [33,[513][514][515][516][517], restoration of pedicle screw fixation [518,519], reinforcement of thoracolumbar burst fractures [520], cancellous bone screws [521,522], in wrist arthrodesis [523] and for fixation of titanium implants [524]. A recent study on a cement augmentation of the femoral neck defect might be found elsewhere [525]. Considering their properties, calcium orthophosphate cements might potentially be applied to reinforce osteoporotic vertebral bodies [512,526].…”
Section: Orthopaedic Applicationsmentioning
confidence: 99%
“…Besides, other successful attempts have been made to use these formulations for calcaneal fractures [509], hip fractures [510,511], augmentation of osteoporotic vertebral bodies [512], distal radius fractures [513], tibial plateau fractures [33,[513][514][515][516][517], restoration of pedicle screw fixation [518,519], reinforcement of thoracolumbar burst fractures [520], cancellous bone screws [521,522], in wrist arthrodesis [523] and for fixation of titanium implants [524]. A recent study on a cement augmentation of the femoral neck defect might be found elsewhere [525]. Considering their properties, calcium orthophosphate cements might potentially be applied to reinforce osteoporotic vertebral bodies [512,526].…”
Section: Orthopaedic Applicationsmentioning
confidence: 99%
“…The advantages of CPC include a fast setting time, excellent moldability and good osteoconductivity (4,(6)(7)(8)(9). The early structural support that CPC offers is beneficial for large bone defects at risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, symptomatic patients complaining of recurrent pain or exhibiting a restricted range of motion in the affected joints are considered for surgical treatment (1,2,4). There are various surgical treatment strategies for benign bone tumors, consisting of curettage, curettage with autologous/allogeneic bone grafting, and curettage with artificial bone grafting (3)(4)(5)(6)(7)(8). Calcium phosphate cement (CPC) is an injectable biocompatible bone substitute that has been used for various applications in orthopedic surgery, due to its easy handling, high mechanical strength and good osteoconductive biological properties (4,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Internal stabilization of fractured or otherwise mechanically destabilized bone oft en occurs in the presence of compromised bone quality. Placement of hardware into bone of reduced mechanical competency can signifi cantly aff ect the performance of the fi xation hardware, and ultimately the clinical outcome.…”
Section: Introductionmentioning
confidence: 99%